The Influence of Behaviour Finance and Demographic Factors on Investment Decision Making Through Risk Tolerance as Mediation - Dovir Siratan, Elkunny; Tannia, Tannia; Reni Susilo, Sophia; Cristia Dewi, Angelia; Dozen, Wily (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Investment decision making is something that is inevitable and a critical moment in determining the success of an investor in making their investment. This research conduct since investment decision making is very difficult to measure and seen directly. Hence, it is necessary to identify various factors that influence investment decision making including demographic factors, behavior finance, and risk tolerance. The type of research is quantitative with a population of all capital market investors who invest in shares on the Indonesia Stock Exchange (IDX), especially the LQ45 index as well as data processing uses AMOS 24. The results showed that demographic factors have an influence which causing specific behavior and tolerance thresholds related to risk, which in turn affect performance and optimization in investment decision making. Investors must also be aware of the existence of behavior finance which is found in the form of behavior or actions caused by psychological factors inherent. On the other hand, the role of risk tolerance also shapes behavior patterns and planning processes related to finance which are described in risk acceptance. Hence, the emergence of identified investor behavior will later make opportunities for momentum and investment strategies that improve the performance and success of their investments as well as the quality of excellent decision making.